A viral envelope as a vehicle for tracer, drug, and gene delivery. - Flexman, J.A (IEEE Engineering in medicine and biology magazine)
Gene and drug encapsulation by a viral vector administered via a systemic injection represents a therapeutic delivery system that is noninvasive and can potentially be targeted to a region of the body. However, an effective way of monitoring biodistribution, both acutely and over the long term, is needed to evaluate new targeting technologies and to tailor patient care in the clinic. A sensitive and dynamic method is needed to compare the effect of various approaches on clearance. Positron emission tomography (PET) imaging can detect radiotracers within the body with high sensitivity, and, in this study, the noninvasive tracking of viral vectors tagged with radioactive fluorine ([F-18]fluoride) is presented